Error management atmosphere, employee career resilience and employee innovation behavior: The mediating role of psychological empowerment - Zheng, Jinsong; Li, Zhongwu; Su, Jiafu (Edelweiss Applied Science and Technology, 2024)
In order to study the specific influence path and mechanism of different dimensions under error management culture on employees’ innovation behavior, this paper takes the perception of error management atmosphere and employee career resilience as independent variables, psychological empowerment is taken as intermediary variable, active innovation motivation is taken as the moderating variable of psychological empowerment and employee innovation behavior, and employee innovation behavior is taken as the dependent variable. This paper systematically discusses the multi-dimensional and multi-level relationships among error management culture, employee occupational resilience, psychological empowerment, active innovation motivation and employee innovation behavior. The research finds that by enhancing employees’ psychological empowerment, that is, making them feel the meaning, self-efficacy, self-determination and influence of work, enterprises can stimulate employees’ intrinsic motivation and encourage them to be more actively involved in innovation activities. This research not only enriches our understanding of how organizational culture shapes the way employees behave, but also reveals the critical role that individual employee traits (such as occupational resilience) and psychological states (such as psychological empowerment) play in the innovation process. This paper provides some suggestions on how to build a culture that encourages innovation and tolerates errors.